School Based Management in Extracurricular Program Development at a Pesantren Based Vocational School - Misbahul Munir; Narjul Ghufron (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
Educational decentralisation in Indonesia grants schools autonomy in planning and implementing programmes to improve educational quality. However, empirical evidence on how pesantren-based vocational schools operationalise this autonomy through structured extracurricular management and what contributions such management makes to student development remains limited. This qualitative case study investigates the school-based management (SBM) model as implemented through extracurricular programmes at SMKS Manbaul Ulum Bondowoso, a vocational school integrated with an Islamic boarding school (pesantren). Data were collected over six months (January–June 2024) through in-depth interviews with eight informants (the school principal, vice-principal for curriculum, vice-principal for student affairs, three extracurricular coaches for Pencak Silat, Taekwondo, and Scouting, and two students), participant observation across 24 sessions, and documentary analysis of programme work plans, activity reports, and administrative decrees. Data were coded against Edwards III’s (1980) four policy implementation variables (communication, resources, disposition, and bureaucratic structure) and Caldwell and Spinks’s (1992) SBM principles. Findings reveal that SMKS Manbaul Ulum implements a four-stage extracurricular SBM cycle planning, implementation, supervision, and evaluation whose distinguishing feature is its dual coordination requirement: every extracurricular activity must receive authorisation from both the school administration and the pesantren foundation, producing a governance architecture adapted to the institution’s dual public-religious accountability. The study identifies scheduling constraints arising from compulsory religious activities and resource limitations as the primary implementation challenges, and documents observable contributions to student discipline, leadership, and social competence. Theoretically, the findings extend SBM theory by demonstrating how the principle of school autonomy operates within a religiously bounded governance environment.